2019
DOI: 10.1103/physrevb.100.235112
|View full text |Cite
|
Sign up to set email alerts
|

Relating bulk to boundary entanglement

Abstract: Quantum field theories have a rich structure in the presence of boundaries. We study the groundstates of conformal field theories (CFTs) and Lifshitz field theories in the presence of a boundary through the lens of the entanglement entropy. For a family of theories in general dimensions, we relate the universal terms in the entanglement entropy of the bulk theory with the corresponding terms for the theory with a boundary. This relation imposes a condition on certain boundary central charges. For example, in 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
(192 reference statements)
0
13
0
Order By: Relevance
“…There are also attempts to calculate the entanglement entropies for disconnected regions using (31). For example, naively taking a uniform cutoff for all the endpoints of multiintervals in CFT 2 will give [18,57] the results of Refs. [30,[41][42][43], which are not correct in general.…”
Section: Discussionmentioning
confidence: 99%
“…There are also attempts to calculate the entanglement entropies for disconnected regions using (31). For example, naively taking a uniform cutoff for all the endpoints of multiintervals in CFT 2 will give [18,57] the results of Refs. [30,[41][42][43], which are not correct in general.…”
Section: Discussionmentioning
confidence: 99%
“…In d = 4, the free energy on a hemisphere [15] (suitably normalized by the round 4-sphere free energy) was proposed and checked in free and perturbative examples to decrease under boundary RG flows. The boundary trace anomaly is also related to the entanglement entropy in the presence of a boundary which has been discussed in [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Note that this evaluation of entanglement entropy using PEE is very subtle for disconnected regions.For example, previous studies[14,51,56] showed that naively taking an uniform cutoff for all the endpoints of multi-intervals in CFT2 will give the results of refs [57][58][59][60],. which is only justified for free fermions while incorrect in more general theories.…”
mentioning
confidence: 99%